Systematic Review: Hubungan Obesitas dengan Risiko Benign Prostat Hiperplasia - Armadani, Melni; Kurniati, Intanri; Hadibrata, Exsa (CV. Jasa Sukses Abadi, 2024)
Benign prostatic hyperplasia (BPH) is a non-malignant growth of prostate tissue. The incidence of BPH is influenced by various risk factors such as metabolic syndrome, obesity, and genetic predisposition. The prevalence of obesity in Indonesia with a male population over 18 years old was recorded at 26.60%. The research used a systematic review method. The databases used are NCBI and PUBMED with bulletions namely Benign prostate hyperplasia AND obesity, Benign prostate hyperplasia AND cholesterol, or Benign prostate hyperplasia AND body mass index. Obesity can trigger pro-inflammatory conditions, one of which is micro vascular disease which results in inflammation triggering ischemia and oxidative stress. Obesity can involve changes in the expression of genes such as A2M in the stroma and TFFB3 in the prostate gland and induce sIL-1ra levels.Obesity is associated with the risk of BPH through inflammatory response mechanisms from cellular and humoral microvascular inflammation, programmed cell death, gene expression and sIL-1ra levels.